2021
DOI: 10.1021/acs.jproteome.0c00904
|View full text |Cite
|
Sign up to set email alerts
|

BioContainers Registry: Searching Bioinformatics and Proteomics Tools, Packages, and Containers

Abstract: BioContainers is an open-source project that aims to create, store, and distribute bioinformatics software containers and packages. The BioContainers community has developed a set of guidelines to standardize the software containers including the metadata, versions, licenses, and/or software dependencies. BioContainers supports multiple packaging and containers technologies such as Conda, Docker, and Singularity. Here, we introduce the BioContainers Registry and Restful API to make containerized bioinformatics… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 18 publications
(58 reference statements)
0
16
0
Order By: Relevance
“…As shown above, we are already working on developing open and reproducible data analysis pipelines for different flavours of proteomics workflows (e.g., DDA, DIA, proteogenomics) ( 49 , 53 , 57 ). The main rationale is to make possible the use of that software in cloud infrastructures so that in the future the pipelines can be used by the community in the cloud using software container technologies ( 58 ).…”
Section: Discussion and Future Plansmentioning
confidence: 99%
“…As shown above, we are already working on developing open and reproducible data analysis pipelines for different flavours of proteomics workflows (e.g., DDA, DIA, proteogenomics) ( 49 , 53 , 57 ). The main rationale is to make possible the use of that software in cloud infrastructures so that in the future the pipelines can be used by the community in the cloud using software container technologies ( 58 ).…”
Section: Discussion and Future Plansmentioning
confidence: 99%
“…Phospholipids include platelet-activating factor (PAF), phosphatidylcholine, and lysophosphatidic acid (LPA). Previous studies (31,32) have shown that PAF induces rat fibroblasts to secrete type I and IV collagen and fibronectin tubular cells, leading to renal fibrosis. Furthermore, LPA exerts therapeutic effects on myoblasts and induces significant expression of connective tissue growth factor.…”
Section: Discussionmentioning
confidence: 95%
“…Docker (https://www.docker.com/) was used to run the bioinformatics software. Docker containers of software were obtained from the BioContainers Registry (Bai et al, 2021).…”
Section: Microscopymentioning
confidence: 99%